2020
DOI: 10.1002/rra.3634
|View full text |Cite
|
Sign up to set email alerts
|

Tributary confluences are dynamic thermal refuges for a juvenile salmonid in a warming river network

Abstract: As rivers warm, cold‐water fish species may alleviate thermal stress by moving into localized thermal refuges such as cold‐water plumes created by cool tributary inflows. We quantified use of two tributary confluence plumes by juvenile steelhead, Oncorhynchus mykiss, throughout the summer, including how trout positioned themselves in relation to temperature within confluence plumes. At two confluences, Cedar and Elder creeks, along the South Fork Eel River, California, USA, we monitored temperatures using in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
1
24
1
Order By: Relevance
“…Thermal heterogeneity influences a wide range of species behavior including their distribution, habitat use, growth and development, and movement patterns (Torgersen et al 1999, Ebersole et al 2003, Armstrong et al 2013). In contrast to previous studies documenting the importance of thermal heterogeneity as coldwater refuges in otherwise warm-water systems (Torgersen et al 1999, Ebsersole et al 2003, Brewitt et al 2017, Fullerton et al 2018, Wang et al 2020, the increases in thermal heterogeneity that we observed added warm-water patches to otherwise cool-water systems. However, it is challenging to predict the effects of this heterogeneity on thermally sensitive ectotherms in these watersheds.…”
Section: Biological Implicationscontrasting
confidence: 99%
“…Thermal heterogeneity influences a wide range of species behavior including their distribution, habitat use, growth and development, and movement patterns (Torgersen et al 1999, Ebersole et al 2003, Armstrong et al 2013). In contrast to previous studies documenting the importance of thermal heterogeneity as coldwater refuges in otherwise warm-water systems (Torgersen et al 1999, Ebsersole et al 2003, Brewitt et al 2017, Fullerton et al 2018, Wang et al 2020, the increases in thermal heterogeneity that we observed added warm-water patches to otherwise cool-water systems. However, it is challenging to predict the effects of this heterogeneity on thermally sensitive ectotherms in these watersheds.…”
Section: Biological Implicationscontrasting
confidence: 99%
“…Sutton, Deas, Tanaka, Soto, and Corum (2007) described thermal refuges as water cooler than 22-23 C for different U.S. West Coast species of salmonids. Wang, Kelson, Greer, Thompson, and Carlson (2020) used a threshold of 21 C and a 2 C difference between the cold plume and main stem temperature to define a refuge for steelhead trout. For Atlantic salmon, Breau, Cunjak, and Bremset (2007) observed aggregations of juveniles in refuges that were defined as having water temperatures colder than 23 C. While Kurylyk, MacQuarrie, Linnansaari, Cunjak, and Curry (2015) explained that Atlantic salmon parr are known to use refuges characterized by temperature differences with the main stem <2 C. In the present study, we determine the boundaries of the cold-water plume using a temperature difference of 1 C with the river main stem.…”
Section: Introductionmentioning
confidence: 99%
“…Wilbur, O'Sullivan, MacQuarrie, Linnansaari, and Curry (2020) compared thermal refuges usage by Brook trout (Salvelinus fontinalis) and Atlantic salmon in New Brunswick river systems (Canada). Statistical approaches have also been used to investigate the presence or distribution of other fish species in refuges (e.g., Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To be consistent with past studies (e.g., Kelson and Carlson 2019) and the California Department of Fish and Wildlife, five WYTs (i.e., very dry, dry, moderate, wet, and very wet) were defined based on annual flow quintiles over the period of record (1967-2019) at the Elder Creek USGS gage (USGS 11475560). Elder Creek is an undammed tributary to the SFER which flows through the Angelo Coast Range Research Reserve-a pristine environment with cool, groundwater-fed tributaries and high-quality habitat in which local researchers have focused significant data collection efforts for decades (e.g., CDFW 2014; Greer et al 2019;Wang et al 2020b). WYTs were assigned to each study year within relationships.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection was clustered spatially in the watershed. Highdensity data collection occurs in a public state park in the northern watershed with a range of channel types, including mainstem (SFE01 and SFE04) and tributary (SFE05 and SFE07) settings, and in a research reserve to the south that has been the focus of significant data collection for decades (e.g., CDFW 2014; Greer et al 2019;Wang et al 2020b) (Fig. 5).…”
Section: Spatial Attributesmentioning
confidence: 99%